Learning from Inuit perspectives on marine governance - McLean, Jeffrey (2021)
Our ocean is undergoing drastic changes. In the circumpolar north, this reality is highly visible. Social-ecological systems thinking informs that social and ecological systems are intertwined, yet hegemonic governance systems appear unable or unwilling to reorient themselves to promote planetary health amidst the climate crisis. To rethink our relationship with the ocean, I explore the research question, “What can I learn from Inuit perspectives about the ocean and marine governance within Inuit Nunangat, and how does this relate to planetary health?” This study applies critical theory methodologies. In particular, feminist standpoint theory informs the approach of engaging with knowledge and lived experience of marginalized or oppressed populations. Inuit knowledge in the form of a purposefully sampled collection of publicly available Inuit documents that relate to the marine environment is the primary evidence that informs analysis. Inuit produced declarations, websites, and reports are analysed using thematic analysis. This study does not depend on ethics review or community engagement; research using publicly available information is exempt from these ethical requirements. Nevertheless, the positionality I strive to embody is allyship with Inuit. Two main themes are interpreted from analysis. First, the meaning of the marine contains the key ideas: Inuit culture relies upon marine ecosystems; rapidly social-ecological systems have cultural implications; and environmental protection focuses on marine areas of significance. A rights-based approach reflects the assertions: Inuit are rightsholders not stakeholders; political equality is still hindered by systems of racism and oppression; and collaborative governance approaches are the path forward. Governance mechanisms that recognize Indigenous rights have the capacity to promote planetary health. Inuit self-determination is health promotion, supporting marine protection, equitable marine governance, and strengthening Inuit culture. Decision-making systems ...